Financial Performance Mediation Model on the Influence of Islamic Corporate Governance on Sustainability Reports Moderated by Corporate Social Responsibility - Musdalifa Musdalifa; Afrizal Afrizal; Mukhzarudfa Mukhzarudfa; Achmad Hizazi (Maneggio, 2026)
This research is motivated by the importance of implementing Islamic Corporate Governance in improving the performance and sustainability of Islamic banking, which still faces various challenges, such as low contribution to the economy and the quality of sustainability reporting. This study aims to analyze the effect of Islamic Corporate Governance on Sustainability Reports, with financial performance as a mediating variable and Corporate Social Responsibility as a moderating variable. This study uses a quantitative approach with secondary data in the form of annual reports and sustainability reports of Islamic Commercial Banks in Indonesia for the period 2019–2024. Data analysis was conducted to test the direct, indirect, and moderating effects between variables in the research model. The results show that Islamic Corporate Governance has a positive and significant effect on financial performance and Sustainability Reports. Financial performance is proven to act as a mediating variable, while Corporate Social Responsibility acts as a moderating variable that strengthens the relationship between governance and sustainability reporting. These findings indicate that the implementation of Sharia-based governance, supported by good financial performance and effective CSR practices, can improve corporate transparency and sustainability. The conclusion of this study confirms that the integration of Islamic Corporate Governance, sharia-based financial performance, and Corporate Social Responsibility is a key factor in improving the quality of Sustainability Reports in Islamic banking in Indonesia.